2014
DOI: 10.1083/jcb.201401090
|View full text |Cite
|
Sign up to set email alerts
|

Direct kinetochore–spindle pole connections are not required for chromosome segregation

Abstract: In the absence of continuous K-fiber attachment between each kinetochore and the spindle pole, one or more additional mechanisms dependent on dynein-mediated kinetochore transport exist to ensure proper chromosome segregation during mitosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
149
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(159 citation statements)
references
References 52 publications
(86 reference statements)
9
149
1
Order By: Relevance
“…NuMA is required for dynein activity and dynactin localization at minusends If NuMA does target dynein-dynactin to minus-ends, localizing force there, we would expect NuMA to be required for dynein to transport minus-ends created by k-fiber ablation (Elting et al, 2014; Sikirzhytski et al, 2014). To test this hypothesis, we made inducible CRISPR/Cas9 RPE1 cell lines to knock out NuMA (Figure 3-figure supplement 1) (McKinley et al, 2015;Wang et al, 2015).…”
Section: Numa Localizes To Minus-ends Independently Of Dyneinmentioning
confidence: 99%
See 1 more Smart Citation
“…NuMA is required for dynein activity and dynactin localization at minusends If NuMA does target dynein-dynactin to minus-ends, localizing force there, we would expect NuMA to be required for dynein to transport minus-ends created by k-fiber ablation (Elting et al, 2014; Sikirzhytski et al, 2014). To test this hypothesis, we made inducible CRISPR/Cas9 RPE1 cell lines to knock out NuMA (Figure 3-figure supplement 1) (McKinley et al, 2015;Wang et al, 2015).…”
Section: Numa Localizes To Minus-ends Independently Of Dyneinmentioning
confidence: 99%
“…In computational models, localizing a minus-end-directed motor at microtubule ends permits microtubule clustering into asters or poles (Foster et al, 2015;Goshima et al, 2005;Nedelec and Surrey, 2001;Surrey et al, 2001) and the emergence of a robust steady-state spindle length (Burbank et al, 2007). More recently, experimental work has shown that dynein-dynactin and NuMA do indeed selectively localize to spindle minus-ends, with dynein pulling on them after kinetochore-fiber (k-fiber) ablation in mammalian spindles (Elting et al, 2014;Sikirzhytski et al, 2014). This is consistent with suggestions that dynein and NuMA capture and pull on distal k-fiber minus-ends in monopolar spindles (Khodjakov et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Nicklas assumed this load was shared by a subset of 15 kinetochore-attached microtubules that extended all the way to spindle pole (out of a total of ~40 kinetochore-attached microtubules), leading to an often-cited estimate of 50 pN per microtubule [59]. This might be an overestimate, with the true value falling closer to 12 pN per microtubule, given the recent work indicating that all kinetochoreattached microtubules, even those that do not extend all the way to a pole, are anchored within the spindle [60,61]. But in either case the forces during a normal, unperturbed anaphase are probably much, much lower still.…”
Section: Anaphase Spindle Generates More Force Than Needed For Anaphamentioning
confidence: 83%
“…Questions also remain about how depolymerase activity is engaged when the motors and minus ends reach the pole. [60,61]. (a) Ablation of a k-fiber (yellow lightning bolt) during anaphase.…”
Section: Potential Biophysical Mechanisms For Kinetochore-microtubulementioning
confidence: 99%
“…Aurora B phosphorylation of Ndc80 reduces its microtubule-binding affinity, which prevents erroneous attachment of kinetochores to microtubules DeLuca et al 2006;Liu et al 2009;Alushin et al 2010;Lampson and Cheeseman 2011;Zaytsev et al 2015). Ndc80 phosphorylation is finely controlled until proper bi-orientation is established under tension during prometaphase (Magidson et al 2011;Sikirzhytski et al 2014). These stable attachments between kinetochores and microtubules are mediated by a feedback mechanism, which balances phosphorylation of Ndc80 by Aurora B and its dephosphorylation by B56-PP2A or PP1 phosphatases (Foley et al 2011;Suijkerbuijk et al 2012).…”
Section: Regulation Of Outer Kinetochore Dynamicsmentioning
confidence: 99%